2009
DOI: 10.1007/s11104-009-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-inoculation of methylotrophic Methylobacterium oryzae with Azospirillum brasilense and Burkholderia pyrrocinia on the growth and nutrient uptake of tomato, red pepper and rice

Abstract: The present greenhouse study was undertaken to evaluate the effects of co-inoculating methylotrophic Methylobacterium oryzae CBMB20 along with nitrogen-fixing Azospirillum brasilense CW903 or a phosphate solubilizing bacterium Burkholderia pyrrocinia CBPB-HOD on the growth and nutrient uptake of tomato, red pepper and rice. Seed inoculation and soil/foliar application of the bacterial strains alone or under dual inoculation increased the plant growth in terms of shoot or root length and increased the nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 29 publications
(33 reference statements)
5
43
1
2
Order By: Relevance
“…Although the positive responses of crop plants to inoculation of A. brasilense CW903 and M. oryzae CBMB20 were clearly demonstrated under controlled conditions (Kim et al, 2011;Madhaiyan et al, 2010;Ryu et al, 2006), in this study conducted under field condition, inoculations of A. brasilense CW903 and M. oryzae CBMB20 were not effective on promotion of the growth and fruit yield of red pepper plant. Bashan et al (2004) suggested that the good positive plant growth-promoting effects obtained under pot experiments cannot always be dependably reproduced under field conditions.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…Although the positive responses of crop plants to inoculation of A. brasilense CW903 and M. oryzae CBMB20 were clearly demonstrated under controlled conditions (Kim et al, 2011;Madhaiyan et al, 2010;Ryu et al, 2006), in this study conducted under field condition, inoculations of A. brasilense CW903 and M. oryzae CBMB20 were not effective on promotion of the growth and fruit yield of red pepper plant. Bashan et al (2004) suggested that the good positive plant growth-promoting effects obtained under pot experiments cannot always be dependably reproduced under field conditions.…”
Section: Resultscontrasting
confidence: 56%
“…These results indicate that the positive plant growthpromoting potential of the inoculants expressed in pot experiments cannot always be reproduced under field conditions. As demonstrated in numerous worldwide trials, we have already found positive effects of A. brasilense CW903 and M. oryzae CBMB20 inoculation on plant growth in the previous laboratory and pot experiments with wheat, rice, red pepper, tomato, canola, and groundnut (Madhaiyan et al, 2004;Madhaiyan et al, 2006a;Madhaiyan et al, 2006b;Madhaiyan et al, 2007;Madhaiyan et al, 2010;Ryu et al, 2006). Plant growth promoting effect of A. brasilense could be attributed to several mechanisms including enhancement of root development, production of growth regulators and nitrogen fixation (Bashan and Holguin, 1997;Kim et al, 2005).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Additionally, inoculants must overcome two major problems inherent to living microorganisms: (1) loss of viability during short storage in the grower's warehouse, and (2) long shelf life and stability of the product over a range of −5 to 30°C, within growers' storage conditions. Anith et al 2004;Bacilio et al 2003Bacilio et al , 2004Bashan et al 2006;Boruah and Kumar 2002;Cakmakci et al 2001Cakmakci et al , 2006Carrillo-Garcia et al 2000;Dominguez-Nuñez et al 2012;Egamberdiyeva 2007;Esitken et al 2003;Fürnkranz et al 2012;Guetsky et al 2002a, b;Guiñazú et al 2010;Hossain and Mårtensson 2008;Jetiyanon et al 2003;Khan et al 2003;Kurek and Jaroszuk-Ściseł 2002;Landa et al 2001;Lopez et al 2013;Madhaiyan et al 2010;Mehnaz et al 2010;Odee et al 2002;Ozturk et al 2003;Puente et al 2004aPuente et al , b, 2009aRajapaksha et al 2011;Singh et al 2011;Sigler et al 2001;Sudhakar et al 2000;Yan et al 2003;Yu et al 2011;Zafar et al 2012 Liquid (culture media or water) Clayton et al 2004a, b;Hamaoui et al 2001;Hungria et al 2010; Bashan et al 2002a, b;deBashan et al 2004;…”
Section: Characteristics Of a Carrier For Inoculants; The Ideal Inocumentioning
confidence: 99%